Kedudukan Sumpah Pemutus dalam Pembuktian Sengketa Tanah Waris - I Gusti Ayu Maha Patni; I Made Suwitra; I Ketut Sukadana (Jurnal Konstruksi Hukum, 2020)
This study is motivated by the phenomenon of inherited land disputes that often occur in the community. When the distribution of inheritance is not fair, the heirs can file a lawsuit in court according to the choice of law, both in western civil law and in customary law. This study aims to determine the procedure for the breaker's oath in inherited land disputes and to analyze the power of proof of the breaker's oath in inherited land disputes. This study uses a normative research method with the aim of analyzing the obscurity of norms regarding the proof of the breaker's oath. The data used comes from legal materials such as statutory regulations, Civil Code, HIR or RBg and Jurisprudence. The results of the analysis show that the procedure for the breaker's oath in inherited land disputes is the breaker's oath (oath decisoir) which is charged at the request of one party to the opponent. The types of breaking oaths or decisoir oaths can be in the form of pocong oaths, pulpit vows, pagoda oaths, and cast oaths which are known in Hindu society in Bali. An oath of decision making in inherited land disputes, namely an oath of decision made when there is no attempt to prove anything in a case. Then, the power of proof of the breaker's oath is seen in Decision Number 148 / PDT.G / 2016 / PN GIN, that the power of proof of the breaker's oath has the power to decide cases or disputes which have the value of perfect proving power, binding and determining